The Development of a Moodle-Assisted Guided Inquiry Model for General Biology E-Learning to Enhance the Student' Critical Thinking Dispositions - Saidil Mursali; Utami Sri Hastuti; Siti Zubaidah; Fatchur Rohman (Jurnal Penelitian Pendidikan IPA, 2023)
Critical thinking disposition is a component of higher-order thinking skills required to meet 21st-century challenges. This research aimed to develop a Moodle-assisted Guided Inquiry model (GI-Moodle) for General Biology e-learning and to enhance university students' critical thinking disposition. Fenrich's instructional model was used in this development research. Meanwhile, a quasi-experimental study was conducted at the implementation stage. This study was carried out at the Faculty of Applied Science and Engineering, Undikma. The data were collected using validation sheets and the California Critical Thinking Disposition Inventory. Descriptive quantitative analysis and ANCOVA were done. The results revealed that: the general biology e-learning developed was reliable and valid; students' critical thinking disposition increased from the pretest to the posttest, where the GI-Moodle students achieved better than the WhatApp Group-assisted Guided Inquiry students (GI-WAG) and WhatApp Group-assisted Structured Inquiry students (SI-WAG);Â the implementation of GI-Moodle and GI-WAG E-learning did not have a significant effect, but it was significantly different compared to the SI-WAG class. In conclusion, GI-Moodle is a viable option for enhancing college students critical thinking disposition through General Biology e-learning. It can be a reference for development in other learning